Analysis of Policies for Organizing and Managing Informal Settlements in Iran: A Content Analysis Method - Naeimeh Poortaheri; Khalil Alimohammadzadeh; Seyed Mojtaba Hosseini; Ali Maher; Mohammadkarim Bahadori (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Due to the increasing growth of informal and marginal settlements in Iran, the present study was conducted to analyze the contents of upstream national documents regarding city slum in Iran. Methods: This qualitative study with content analysis approach was done in 2020. MAXQDA version 12 software and conventional content analysis method was used to analyze the data. Results: The findings of this study could be classified in two main categories and 11 subcategories. The main categories included the policies related to preventing the creation of slum areas, and policies related to providing service and rehabilitation of slum areas. The 11 subcategories  included preventing migration from inner cities to slum areas, poverty alleviation, preserving the rural fabric through the village guide plan, balanced distribution of population with landscaping and land development approach, creating green belts around cities, forced confrontation with illegal constructions in slum areas, impulsive phenomenon of social harms, allocation of state financial facilities to organize informal settlements, renovation of informal settlements, creating satellite towns, and providing primary health care services in the form of  health care network system. Conclusion: Although providing service and rehabilitation of slum areas can play an important role in reducing harm in these areas, policymakers in Iran should be aware of a moral dilemma; since these policies can also encourage the phenomenon of city slum.